Corruption Prevention Model Through Integrated Education (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The research examines: (i) the ideal form of preventing corruption through an integrated education system; and (ii) projected obstacles to implementing the corruption prevention model through an integrated education system. The background to the existence of criminal acts of corruption is proven by Indonesia's position at rank 96 out of 180 countries with a score of 38 out of a perfect score of 100 at the beginning of 2023, below the global nominal of 43. Data proves that efforts to eradicate corruption by optimizing the penal system have not been effective in preventing the rate of corruption cases. Non-penal steps are needed, one of which is through anti-corruption education by instilling awareness of the impact of corruption in the younger generation. The research uses a conceptual approach, then combined with legal material and qualitative thinking analysis. The research results show that there are three ideal forms of preventing corruption through an integrated education system, namely: (i) providing basic level anti-corruption education; (ii) preparation of an anti-corruption education curriculum; and (iii) preparation of anti-corruption educational learning schemes. Meanwhile, obstacles include: (i) there is no anti-corruption education curriculum; (ii) implementation instructions and technical instructions for implementing integrated anti-corruption education are not yet available; and (iii) Anti-corruption education is facultative.